Factors of Using Non-Cash Payments to the Consumption Level of Students in Pematangsiantar City - Yerisma Welly; Supitriyani Supitriyani; Yusnaini Yusnaini; Acai Sudirman (Jurnal Bisnis dan Manajemen, 2020)
This study aims to determine the factors of the use of non-cash payments to the consumption levels of Pematangsiantar City students. In this study the level of student consumption as the dependent variable and the factors of using non-cash payments are perceived usefulness, perceivedease of use and perceived trust as independent variables. The population in this study were students of Accounting Department in the seventh semester at STIE Sultan Agung Pematangsiantaras many 167 people. This study used quantitative data in the form of a questionnaire. Data analysis techniques used in this research are classic assumption test, multiple linear regression, determination test, F test and t test.The results showed that the perceived usefulness, perceived ease of use and perceived trust had a positive and significant effect on student consumption levels. This is because students prefer to make any purchases (consumption) using non-cash payments. The benefits of non-cash payments can be used anywhere, easy to carry, more secure and has trust in the accuracy of the transactions made